Roy Rabb och anakronismen - Klinkmann, Sven-Erik (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2014)
This text deals with anachronism, within the framework of a cultural analytical research effort, in the life and art of Ostrobothnian dance band musician and local politician Roy Rabb. The intention here is to activate a critical thinking on anachronisms, what they do and why it seems that we need them. The arenas and artefacts studied are Roy Rabb’s activities as a dance band musician, his laptop, steel guitar and his sports car, and also his engagement in the populist party the True Finns. The playfully subversive character of many of Rabb’s musical and visual undertakings makes it difficult to place his anachronisms within an unambiguously national or nationalistic context. But on the other hand, some remarks he has been making, of an openly racist and male chauvinistic nature, indicates a certain caution as to a reading the anachronisms of Roy Rabb strictly along the lines of a playful subversiveness.